2015
DOI: 10.1021/acscatal.5b00333
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and Computational Study of Cr Oxide Structures and Their Anchoring Sites on ZSM-5 Zeolites

Abstract: Cr/ZSM-5 catalysts with 0.5−2.6 wt % Cr loadings and zeolites with 15−140 Si/Al ratios were characterized with in situ UV−vis, IR, and Raman spectroscopies, including operando Raman measurements under reaction conditions in methane conversion at 773−1123 K with a simultaneous online analysis of reaction products. DFT calculations with cluster and periodic models were performed with DMol 3 , Gaussian 09, and VASP software packages. Isolated Cr(VI) dioxo and Cr(III) mono-oxo structures on framework Al anchoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 49 publications
3
65
0
Order By: Relevance
“…The spectroscopic properties of Cr 6+ on Al 2 O 3 are well known in the specialized literature. While for Cr 6+ on SiO 2 there is still a debate on the aggregation state of the Cr 6+ species (both mono-and dichromates have been proposed [5, 7-9, 20, 22-24, 26, 34, 35], or even mono-oxo CrO 5 [27][28][29][30][31][32][33]), Cr 6+ exist primarily as monochromate species on Al 2 O 3 [9,[19][20][21][22][23][24]36] (the corresponding DR UV-Vis-NIR spectrum is shown in Figure S1a). Temperature-programmed reduction measurements have demonstrated that Cr 6+ on Al 2 O 3 are more reducible than Cr 6+ on SiO 2 (i.e.…”
Section: The Role Of Co and H 2 As Reducing Agents For Cr 6+ /Al 2 Omentioning
confidence: 99%
“…The spectroscopic properties of Cr 6+ on Al 2 O 3 are well known in the specialized literature. While for Cr 6+ on SiO 2 there is still a debate on the aggregation state of the Cr 6+ species (both mono-and dichromates have been proposed [5, 7-9, 20, 22-24, 26, 34, 35], or even mono-oxo CrO 5 [27][28][29][30][31][32][33]), Cr 6+ exist primarily as monochromate species on Al 2 O 3 [9,[19][20][21][22][23][24]36] (the corresponding DR UV-Vis-NIR spectrum is shown in Figure S1a). Temperature-programmed reduction measurements have demonstrated that Cr 6+ on Al 2 O 3 are more reducible than Cr 6+ on SiO 2 (i.e.…”
Section: The Role Of Co and H 2 As Reducing Agents For Cr 6+ /Al 2 Omentioning
confidence: 99%
“…In this work, the outlet molar flow rates of C1 to C6 n-alkanes and C2 to C5 1-alkenes were used as responses in eq [6]. The statistical weights, , are calculated from the inverse of the covariance of the experimental errors, eq [7].…”
Section: Regression Analysismentioning
confidence: 99%
“…Initial estimates for the are determined from the inverse of calculated by eq [1]. The final regression was performed using the weights of eq [7] as only at a few experimental conditions replicate experiments were available.…”
Section: Regression Analysismentioning
confidence: 99%
See 2 more Smart Citations